Electrostatic self-assembly of MXene and carbon nanotube@MnO2 multilevel hybrids for achieving fast charge storage kinetics in aqueous asymmetric supercapacitors. Issue 44 (2nd November 2022) - Li, Shulong; Peng, Zhongyou; Huang, Yuting; Tan, Licheng; Chen, Yiwang
Abstract : A Ti3 C2 T z /CNT@MnO2 film with a unique structure, strong interfacial interaction and synergy was prepared by electrostatic self-assembly for state-of-the-art aqueous supercapacitors. Abstract : Nanostructured birnessite (δ-MnO2 ) has a high specific capacitance and virtually perfect capacitive behaviors as an essential electrode material for high-power energy storage devices. However, simultaneously achieving excellent capacitive properties and adequate structural stability is particularly challenging. Herein, a conductive and freestanding pseudocapacitive electrode (Ti3 C2 T z /CNT@MnO2 abbreviated as TCM) is fabricated by electrostatically assembling Ti3 C2 T z nanosheets and δ-MnO2 in situ grown on carbon nanotubes (CNT@MnO2 ). Benefitting from the unique structure, strong interfacial interactions and synergistic effects between Ti3 C2 T z nanosheets and CNT@MnO2, the TCM electrode shows a high capacitance value (384 F g −1 at 0.5 A g −1 ), excellent rate capability, and superior stability (92.2% retention after 10 000 cycles). The outstanding capacitive charge storage of TCM originates from reversible Na + intercalation/deintercalation, according to electrochemical quartz crystal microbalance (EQCM) and in situ Raman spectroscopy. Remarkably, an assembled asymmetric supercapacitor (ASC) based on the TCM film and nitrogen-doped reduced graphene oxide (NRGO) delivers landmark energy/power densities (44 W h kg −1 and 43.4 kW kg −1 ) and ultra-long cycle performance. Furthermore, the ASC exhibits a high voltage of 2.4 V with an impressive energy density of 58 W h kg −1 in 10 M NaClO4 salt-in-water electrolyte. This work offers a vital insight and clues to engineering stable birnessite materials for aqueous supercapacitors.